2019
DOI: 10.1097/phh.0000000000000711
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Child Lead Exposure in a Philadelphia Community, 2014

Abstract: Entryway floor dust lead levels were strongly associated with blood lead levels in participants. Results underscore the importance to make housing lead safe by addressing all lead hazards in and around the home. Reduction of child lead exposure is crucial, and continued blood lead surveillance, testing, and inspection of homes of children with BLLs of 5 μg/dL or more to identify and control lead sources are recommended. Pediatric health care providers can be especially vigilant screening Medicaid-eligible/enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 13 publications
4
13
0
3
Order By: Relevance
“…The proportion of Pueblo children with reportable BLL was more than two times higher when children lived near the main old smelter versus away (13.9% vs. 6.4%), further stressing the public health risks associated with these industrial activities. Our results are consistent with a recent report that 12.4% of 104 children tested in a Philadelphia community, with a history of lead-emitting industrial activities, had reportable BLLs or higher [ 47 ].…”
Section: Discussionsupporting
confidence: 93%
“…The proportion of Pueblo children with reportable BLL was more than two times higher when children lived near the main old smelter versus away (13.9% vs. 6.4%), further stressing the public health risks associated with these industrial activities. Our results are consistent with a recent report that 12.4% of 104 children tested in a Philadelphia community, with a history of lead-emitting industrial activities, had reportable BLLs or higher [ 47 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, we performed a road dust and soil investigation, which identified legacy Pb paint and leaded gasoline as the main contributors to Pb pollution in the city (e.g., [26]). Another study in Philadelphia found that higher childhood EBLL were strongly related to Pb content in entryway floor dust [63]. Overall, the authors were not able to directly identify a single point source related to childhood EBLL.…”
Section: Introductionmentioning
confidence: 91%
“…[64]). Living near a mine and spoil or a metal-emitting industry put people at risk of exposure to PM and associated metals ('neighbourhood exposure') [35]. Elderly people exposed to mining waste, which is often open to being spread widely by wind and rain, suffer a disproportionate burden of lung diseases [78•].…”
Section: Environmental Determinantsmentioning
confidence: 99%